(untitled) (Analysis in Theory and Applications, 2023)
Lutwak showed the Busemann-Petty type problem (also called the Shephard type problem) for the centroid bodies. Grinberg and Zhang gave an affirmation and a negative form of the Busemann-Petty type problem for the L_p-centroid bodies. In this paper, we obtain an affirmation form and two negative forms of the Busemann-Petty type problem for the general L_p-centroid bodies.